1998
DOI: 10.1074/jbc.273.8.4747
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Propeptide for Processing and Sorting of Human Myeloperoxidase

Abstract: Myeloperoxidase (MPO), stored in azurophil granules of neutrophils, is critical for an optimal oxygen-dependent microbicidal activity of these cells. Pro-MPO goes through a stepwise proteolytic trimming with elimination of an amino-terminal propeptide to yield one heavy and one light polypeptide chain. The propeptide of MPO may have a role in retention and folding of the nascent protein into its tertiary structure or in targeting of pro-MPO for processing and storage in granules. A propeptide-deleted pro-MPO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…2), suggesting that normal amounts of the G501S precursor entered the secretory pathway despite the failure of proteolytic maturation to proceed. As reported previously for normal MPO biosynthesis (20), ϳ10% of MPO precursor is secreted constitutively and undergoes limited modification of its oligosaccharide side chains during transit through the Golgi, whereby the secreted species is partially resistant to endoglycosidase H digestion (39). To determine whether the secreted MPO precursor from transfectants expressing G501S underwent oligosaccharide modification, the lysates of pulselabeled cells and supernatants conditioned by the 20-h chase period were recovered from each cell line, immunoprecipitated with MPO antiserum, and subjected to digestion with endoglycosidase H or N-glycanase to cleave high mannose or both high mannose and complex mannose side chains, respectively.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…2), suggesting that normal amounts of the G501S precursor entered the secretory pathway despite the failure of proteolytic maturation to proceed. As reported previously for normal MPO biosynthesis (20), ϳ10% of MPO precursor is secreted constitutively and undergoes limited modification of its oligosaccharide side chains during transit through the Golgi, whereby the secreted species is partially resistant to endoglycosidase H digestion (39). To determine whether the secreted MPO precursor from transfectants expressing G501S underwent oligosaccharide modification, the lysates of pulselabeled cells and supernatants conditioned by the 20-h chase period were recovered from each cell line, immunoprecipitated with MPO antiserum, and subjected to digestion with endoglycosidase H or N-glycanase to cleave high mannose or both high mannose and complex mannose side chains, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…Heme acquisition was necessary for exit from the ER and for proteolytic processing to mature subunits, with the latter event inhibited by disruption of the Golgi by treatment with brefeldin A (data not shown). Approximately 10% of MPO precursor entered the secretory pathway and underwent limited modification of its oligosaccharide side chains, as seen with MPO endogenously produced by cultured promyelocytes (39). The spectral properties of MPO-enriched pellets recovered from stable transfectants were identical to those of normal MPO (see below), with a max of 430 nm for the oxidized sample and a Soret band at 473 nm for the reduced minus oxidized spectroscopy (41).…”
Section: Activity Of G501s Precursors Expressed In K562mentioning
confidence: 82%
See 1 more Smart Citation
“…Wild-type MPO is targeted for storage in granules by a regulated pathway, or secreted outside the cell by a constitutive pathway (43). Detailed studies on the role of the propeptide in maturation and sorting of MPO in myeloid 32D cell line revealed that MPODpro was effectively transported to the culture medium by the secretory pathway, but the intracellular trafficking to the storage granules was completely blocked (48). Therefore, the propeptide is likely to have an important role in the proper cellular sorting of MPO.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-regions of neutrophil elastase and cathepsin G are not critical for sorting nascent protein to the azurophilic granule when expressed in cultured rat or murine cell lines [14,15]. On the other hand, the pro-region of myeloperoxidase directs a glycosylated construct of lysozyme to lysosomes when transfected into Chinese hamster ovary cells [16], and constructs with the pro-region deleted fail to undergo normal proteolytic maturation and targeting when expressed in murine cells [17]. The extent to which the experimental system, viz.…”
Section: Inflammation Program and Departments Of Medicine Universitymentioning
confidence: 99%